CONTRIBUTION TOWARDS THE KNOWLEDGE OF THE SPECIES OF THE GENUS ACANTHODOTHECA TOWNSEND DIPTERASARCOPHAGIDAE - SOUZA LOPEZ, H DE; DOWNS WILBUR, G (Instituto Politécnico Nacional, Escuela Nacional de Ciencias Biológicas, CD MEXICO, DF, MEX, 1930)
Redescr of males of A prohibita, A rudis, A excisa, A dampfi, A lanei, A alcedo, and A a denieri; genus is givendescrs of A inornata, A i ssp pauciseta , A exuberans, A alcedo ssp minense , and A acridiophagoides from Brazil, and A azteca
MEM INST OSWALDO CRUZ
Keywords: CONTRIBUTION, KNOWLEDGE, SPECIES, GENUS, ACANTHODOTHECA, DIPTERASARCOPHAGIDAE; CIENCIAS MEDICAS; PATOLOGIA; PATOLOGIA EXPERIMENTAL